Ensuring Equity, Diversity, and Inclusion in Academic Surgery: An American Surgical Association White Paper. Issue 3 (September 2018) - West, Michaela A.; Hwang, Shelley; Maier, Ronald V.; Ahuja, Nita; Angelos, Peter; Bass, Barbara L.; Brasel, Karen J.; Chen, Herbert; Davis, Kimberly A.; Eberlein, Timothy J.; Fong, Yuman; Greenberg, Caprice C.; et al.
Abstract : Objective: The leadership of the American Surgical Association (ASA) appointed a Task Force to objectively address issues related to equity, diversity, and inclusion with the discipline of academic surgery. Summary of Background Data: Surgeons and the discipline of surgery, particularly academic surgery, have a tradition of leadership both in medicine and society. Currently, we are being challenged to harness our innate curiosity, hard work, and perseverance to address the historically significant deficiencies within our field in the areas of diversity, equity, and inclusion. Methods: The ASA leadership requested members to volunteer to serve on a Task Force to comprehensively address equity, diversity, and inclusion in academic surgery. Nine work groups reviewed the current literature, performed primary qualitative interviews, and distilled available guidelines and published primary source materials. A work product was created and published on the ASA Website and made available to the public. The full work product was summarized into this White Paper. Results: The ASA has produced a handbook entitled: Ensuring Equity, Diversity, and Inclusion in Academic Surgery, which identifies issues and challenges, and develops a set of solutions and benchmarks to aid the academic surgical community in achieving these goals. Conclusion: Surgery must identify areas for improvement and work iteratively to address and correct past deficiencies. This requires honest and ongoing identification and correction of implicit and explicit biases. Increasing diversity in our departments, residencies, and universities will improve patient care, enhance productivity, augment community connections, and achieve our most fundamental ambition—doing good for our patients.